Illuminating Women's Hidden Contribution to Historical Theoretical Population Genetics. Issue 2 (3rd November 2018) - Dung, Samantha Kristin; López, Andrea; Barragan, Ezequiel Lopez; Reyes, Rochelle-Jan; Thu, Ricky; Castellanos, Edgar; Catalan, Francisca; Huerta-Sánchez, Emilia; Rohlfs, Rori V
Abstract: Through careful review of one eminent journal over the 1970s and 80s, Dung et al. found a surprisingly high proportion of the computational work was carried out by women. Consistent with authorship norms of the time... While productivity in academia is measured through authorship, not all scientific contributors have been recognized as authors. We consider nonauthor "acknowledged programmers" (APs), who developed, ran, and sometimes analyzed the results of computer programs. We identified APs in Theoretical Population Biology articles published between 1970 and 1990, finding that APs were disproportionately women ( P = 4.0 × 10 −10 ). We note recurrent APs who contributed to several highly-cited manuscripts. The occurrence of APs decreased over time, corresponding to the masculinization of computer programming and the shift of programming responsibilities to individuals credited as authors. We conclude that, while previously overlooked, historically, women have made substantial contributions to computational biology. For a video of this abstract, see: https://vimeo.com/313424402 .